Unique Gene Expression Signatures in the Intestinal Mucosa and Organoids Derived from Germ-Free and Monoassociated Mice - Janeckova, Lucie; Kostovcikova, Klara; Svec, Jiri; Stastna, Monika; Strnad, Hynek; Kolar, Michal; Hudcovic, Tomas; Stancikova, Jitka; Tureckova, Jolana; Baloghova, Nikol; Sloncova, Eva; Galuskova, Katerina; et al. (International journal of molecular sciences, 2019)
Commensal microbiota contribute to gut homeostasis by inducing transcription of mucosal genes. Analysis of the impact of various microbiota on intestinal tissue provides an important insight into the function of this organ. We used cDNA microarrays to determine the gene expression signature of mucosa isolated from the small intestine and colon of germ-free (GF) mice and animals monoassociated with two E. coli strains. The results were compared to the expression data obtained in conventionally reared (CR) mice. In addition, we analyzed gene expression in colon organoids derived from CR, GF, and monoassociated animals. The analysis revealed that the complete absence of intestinal microbiota mainly affected the mucosal immune system, which was not restored upon monoassociation. The most important expression changes observed in the colon mucosa indicated alterations in adipose tissue and lipid metabolism. In the comparison of differentially expressed genes in the mucosa or organoids obtained from GF and CR mice, only six genes were common for both types of samples. The results show that the increased expression of the angiopoietin-like 4 (Angptl4) gene encoding a secreted regulator of lipid metabolism indicates the GF status.
Keywords: Immunity, Mucosal; Animals; Intestinal Mucosa; gnotobiologické modely; kolon; imunitní systém; expression profiling; biologické markery; Escherichia coli; Biomarkers; Onecut2; Immune System; Colon; Microbiota; Mice, Inbred BALB C; stanovení celkové genové exprese; microbiota; Enricher tool; Organoids; regulace genové exprese; mikrobiota; Germ-Free Life; organoidy; myši inbrední BALB C; monoassociation; Gene Expression Regulation; zvířata; slizniční imunita; Gene Expression Profiling; střevní sliznice